The molecular tug of war between immunity and fertility: Emergence of conserved signaling pathways and regulatory mechanisms - Naim, Nikki (Bioessays, 2020)
Reproduction and immunity are energy intensive, intimately linked processes in most organisms. In women, pregnancy is associated with widespread immunological adaptations that alter immunity to many diseases, whereas, immune dysfunction has emerged as a major cause for infertility in both men and women. Deciphering the molecular bases of this dynamic association is inherently challenging in mammals. This relationship has been traditionally studied in fast-living, invertebrate species, often in the context of resource allocation between life history traits. More recently, these studies have advanced our understanding of the mechanistic underpinnings of the immunity-fertility dialogue. Here, we review the molecular connections between reproduction and immunity from the perspective of human pregnancy to mechanistic discoveries in laboratory organisms. We focus particularly on recent invertebrate studies identifying conserved signaling pathways and transcription factors that regulate resource allocation and shape the balance between reproductive status and immune health.